2018
DOI: 10.29070/15/57254
|View full text |Cite
|
Sign up to set email alerts
|

To Investigate the Relationship between CSR of Companies and Their Market Valuation (Equity Valuation): Northern India

Abstract: Corporate Social Responsibility (CSR) has been widely studied in the past with little success on direct impact on firm's valuation. The following research investigates the relationship between CSR of companies and their market value a case study of 20 large size companies in Northern India that are listed in National Securities Exchange (NSE). The research uses secondary data for primary analysis and applies MS Excel to analyze data. The data was collected from annual company reports and NSE website for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The research suggests that investors in Indonesia place a strong emphasis on prioritising sustainable environmental practises. The findings of this investigation are consistent with the conclusions of parallel studies conducted by Budiman and Supatmi (2009), Loh and Tan (2020), and Mittal and Sandhu (2018). Economic growth is a vital factor that determines the rise in the value of firms, as indicated by the growth in market value.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The research suggests that investors in Indonesia place a strong emphasis on prioritising sustainable environmental practises. The findings of this investigation are consistent with the conclusions of parallel studies conducted by Budiman and Supatmi (2009), Loh and Tan (2020), and Mittal and Sandhu (2018). Economic growth is a vital factor that determines the rise in the value of firms, as indicated by the growth in market value.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that, in accordance with the value-enhancing approach, companies that implement and disclose sustainability practises will be more appealing to investors. Mittal and Sandhu (2018) conducted a quantitative study in India and determined that corporations can enhance their valuation by leveraging their corporate social responsibility (CSR) initiatives.…”
Section: Quality Of Sustainability Reportingmentioning
confidence: 99%
“…This indicates that in line with value-enhancing theory, firms that practice and reporting sustainability dimension will attract more investors. In India, Mittal and Sandhu (2018) conducted quantitative research and concluded that companies could rely on their CSR activities to improve their valuation. Also, Daszynska-Zygadlo et al (2016) assert that there is a value increase attached to CSR activities of firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Market value is the current quoted price for market-traded security (Hidayah, 2014). Market value is usually referred to as market capitalisation for quoted companies (Ehrhardt and Brigham, 2011; Mittal and Sandhu, 2018; Shuaibu et al , 2019). It is obtained by multiplying the number of outstanding shares by the current share price.…”
Section: Literature Reviewmentioning
confidence: 99%